2001
DOI: 10.1086/322595
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Anaerobic Bloodstream Infections in Bone Marrow Transplant Recipients

Abstract: The incidence of anaerobic bloodstream infections (BSI) in patients who underwent bone marrow transplantation (BMT) recently increased at our institution. A retrospective case-control study of patients undergoing BMT from January 1995 through December 1998 was performed to determine the microbiological characteristics, epidemiology, and outcome of anaerobic BSI and to identify independent risk factors for infection. Anaerobic BSI occurred in 23 patients, for a rate of 4 BSIs per 100 BMT procedures, and it acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
56
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 14 publications
4
56
0
3
Order By: Relevance
“…Anaerobic BSIs have increasingly been recognized as an important sequela of high-dose chemotherapy, with severe alimentary tract mucositis identified as a predisposing risk-factor (11). While members of the genus Leptotrichia have been isolated from neutropenic patients (1,6,(12)(13)(14)19), they likely remain an underappreciated cause of BSI due to inherent difficulties with conventional laboratory identification methods (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaerobic BSIs have increasingly been recognized as an important sequela of high-dose chemotherapy, with severe alimentary tract mucositis identified as a predisposing risk-factor (11). While members of the genus Leptotrichia have been isolated from neutropenic patients (1,6,(12)(13)(14)19), they likely remain an underappreciated cause of BSI due to inherent difficulties with conventional laboratory identification methods (12).…”
Section: Discussionmentioning
confidence: 99%
“…HSCT recipients are at particularly high risk for the development of invasive bacterial infections as a result of regimen-related neutropenia and cytotoxic damage to the oral and gastrointestinal mucosa. Mucositis severity, specifically, is an independent predictor of anaerobic bloodstream infection (BSI) following HSCT (11).…”
mentioning
confidence: 99%
“…Severe OM interferes with daily activities such as speaking, eating and swallowing and has a negative impact on quality of life. 3,4 It can lead to dehydration, malnutrition and serious infections [5][6][7][8] and has been linked to inferior overall survival (P ÂŒ 0.002) after SCT. 6 Several US-based analyses from various cancer settings have demonstrated that severe OM increases healthcare resource utilization by necessitating opioid analgesia, antiinfective treatment, total parenteral nutrition (TPN) and subsequently prolonging hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…29 We speculate that the dominant biologic processes operative during days 1-10 post transplant are gut mucosal damage, translocation of bacteria and endotoxin, and stimulation of innate immunity. 10,30 The gut mucosa is a site of acute phase protein and pro-inflammatory cytokine production in response to inflammation, sepsis, severe injury and other critical and chronic illnesses. [31][32][33] However, in the weeks before engraftment, we cannot be sure that donor alloimmune cells are not amplifying the inflammatory response despite their relatively small numbers.…”
Section: Discussionmentioning
confidence: 99%